COVID-19 immunization phase; Acceptance & understandings about the vaccine. - Nesar, Shagufta; Rafiq, Kiran; Perveen, Shaheen; Mumtaz, Tayyaba (International Journal of Endorsing Health Science Research, 2021)
Background: In the current scenario of global immunization against Coronavirus, people do have an uncertain thought regarding the efficacy and effects of the vaccine. The purpose of this study was to assess the knowledge, awareness, and acceptability of vaccines among the general population of Karachi. Methodology: For the purpose of the study, literature focusing on the knowledge, awareness, and acceptance regarding COVID-19 immunization was reviewed. Google Scholar, PubMed, Research Gate, and Scopus were searched using the keywords COVID-19, non-pharmaceutical Interventions, immunization-related knowledge, awareness, and acceptance. A pilot study was designed to demonstrate the COVID-19 immunization understanding and acceptability. Results: Low rate of acceptability for getting vaccinated is observed in the local population. Most perceptions indicated vaccines to be not healthy, harmful, and life-threatening. Conclusion: The current situation of fast-spreading of the virus and the non-acceptance of vaccines is highly alarming for community and health authorities and demands strong health care measures and campaigns to control the disaster.